Use of low-power laser to assist the healing of traumatic wounds in rats - Calisto,Fernanda Camila Ferreira da Silva (2015)
PURPOSE: To investigate the morphological aspects of the healing of traumatic wounds in rats using low-power laser.METHODS:Twenty four non isogenic, young adult male Wistar rats (Rattus norvegicus) weighing between 200 and 300g was used. The animals were randomly distributed into two groups: Control (GC) and Laser (GL), with 12 animals each. After shaving, anesthesia was performed in the dorsal region and then a surgical procedure using a scapel was carried out to make the traumatic wound. GL received five sessions of laser therapy in consecutive days using the following laser parameters: wavelength 660 nm, power 100 mW, dose 10 J/cm2. The wounds were evaluated through measurement of the area and depth of the wound (MW) and histological analysis (HA).RESULTS:When comparing the GC with the GL in MW there was a difference in area (p<0.001) and depth (p=0.003) measurement of the wounds in GL. The laser group presented more epithelization than GC (p=0.03). The other histological parameters were similar.CONCLUSION:The healing of wounds in rats was improved with the use of the laser.